(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The type of research in this thesis is experimental research. This study aims to determine: 1) The effect of half squat jump training on shooting accuracy in futsal players of SMA Negeri 8 Makassar; 2) The effect of training without half squat jump on shooting accuracy in futsal players of SMA Negeri 8 Makassar; and 3) The difference in the effect of half squat jump training and without half squat jump on shooting accuracy in futsal players of SMA Negeri 8 Makassar. The population in this study was futsal athletes of SMA Negeri 8 Makassar, with a sample of 40 athletes, with a total sampling technique using Total sampling and a group division system using matching ordinal pairing. The research instruments used were descriptive analysis, data normality analysis, homogeneity analysis, and t-test analysis with the help of the SPSS version 20.00 application. The results of the study showed that; (1) There is an effect of half squat jump training on shooting accuracy in futsal players at SMA Negeri 8 Makassar as evidenced by an increase from an average value of 8.4000 to 15.4000 with an observation value of 10.405 > t table 2.093 and a significant value of 0.000 < α0.05; (2) There is an effect of training without half squat jumps on shooting accuracy in futsal players at SMA Negeri 8 Makassar as evidenced by an increase in the average value8.4000 increased to 11.7000 with an observation value of -4.931 > t-table 2.093 and a significant value of 0.000 < α0.05; (3) There is a difference in the influence between half squat jump training and training without half squat jump on shooting accuracy in futsal players at SMA Negeri 8 Makassar with a difference value of 15.4000 > 11.7000 with an observation value of 4.665 > t-table 2.024 and a significant value of 0.019 < α0.05. The conclusion is that half squat jump training has a greater influence compared to training without half squat jump on shooting accuracy in futsal players at SMA Negeri 8 Makassar.